Using Free and Open Source Tools to Manage Software Quality. - DOWLING, PHELIM; MCGRATH, KEVIN (Communications of the ACM, 2015)
The article explores the free and open source applications and tools used by the research institute Telecommunications Software & Systems Group (TSSG) to build process and quality around its projects and products. Topics discussed include the rollout of Redmine as the organization's primary tool for project management and issue tracking, the institute's use of locally hosted versions of both the Apache Subversion system and the Git repository, and its implementation of Selenium 2.0 WebDriver on a Windows server.